2011
DOI: 10.1007/s10565-011-9186-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interactions between several species of harmful algae and haemocytes of bivalve molluscs

Abstract: Harmful algal blooms (HABs) can have both lethal and sublethal impacts on shellfish. To understand the possible roles of haemocytes in bivalve immune responses to HABs and how the algae are affected by these cells (haemocytes), in vitro tests between cultured harmful algal species and haemocytes of the northern quahog (= hard clam) Mercenaria mercenaria, the soft-shell clam Mya arenaria, the eastern and Pacific oysters Crassostrea virginica and Crassostrea gigas and the Manila clam Ruditapes philippinarum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 77 publications
5
57
0
1
Order By: Relevance
“…Altogether, these data support a mechanism for PST-induced apoptosis in bivalve hemocytes that is independent of ROS production. This observation is consistent with previous studies showing that exposure of C. gigas hemocytes to the PSTproducer, Alexandrium minutum, and purified STX decreased ROS production (Hegaret et al 2011;Mello et al 2013). Thus, the PST-induced death of hemocytes may result from a ligandreceptor interaction rather than a response to oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Altogether, these data support a mechanism for PST-induced apoptosis in bivalve hemocytes that is independent of ROS production. This observation is consistent with previous studies showing that exposure of C. gigas hemocytes to the PSTproducer, Alexandrium minutum, and purified STX decreased ROS production (Hegaret et al 2011;Mello et al 2013). Thus, the PST-induced death of hemocytes may result from a ligandreceptor interaction rather than a response to oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that PSTproducing algae increase the mortality of C. gigas hemocytes both in vitro (Hegaret et al 2011;Lassudrie et al 2016) and in vivo (Medhioub et al 2013). However, fundamental features of this process, including key mechanistic details of how specific PSTs cause toxicity, remained poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulation of P. minimum cells by Ruditapes philippinarum hemocytes has been also suggested by Hégaret et al (2009). Similarly, aggregates of Mercenaria mercenaria hemocytes surrounding P. minimum cells when exposed in vitro have been observed by Hégaret (2007) and Hégaret et al (2008b). Results of the present and previous studies support the hypothesis that hemocytes migrate into the lumina of digestive organs to remove A. minutum cells and/or to protect tissues from toxicity.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have highlighted effects of harmful-algal species upon bivalve hemocytes (Hégaret and Wikfors, 2005a, b;Hégaret et al, 2007a, b;da Silva et al, 2008;Ford et al, 2008;Galimany et al, 2008a, b). Specifically, the dinoflagellate Prorocentrum minimum has been shown to cause morphological and functional changes in hemocytes of several bivalve species (Hégaret and Wikfors, 2005a, b;Galimany et al, 2008a;Hégaret et al, 2008bHégaret et al, , 2009). This dinoflagellate is present throughout the world (Heil et al, 2005) and has been reported to affect filtration, growth, survival, or organ and tissue development of northern quahogs, bay scallops and juvenile eastern oysters (Leibovitz et al, 1984;Shumway et al, 1985;Luckenbach et al, 1993;Wikfors and Smolowitz, 1993, reviewed in Wikfors (2005).…”
Section: Introductionmentioning
confidence: 99%